FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN LANSIA KE POSYANDU MAWAR DI DESA PENDALIAN KECAMATAN PENDALIAN IV KOTO - Fitria; Elvira Junita (Maternity and Neonatal : Jurnal Kebidanan, 2026)
Elderly Posyandu is an Integrated Service Post for elderly people known as Elderly Posyandu. The purpose of Posyandu for the elderly besides getting health services for the elderly, the elderly also get social services, religion, skills, sports and arts and culture as well as other services needed by the elderly in order to improve their quality of life through improving their health and welfare in the community. Along the way, the number of visits to the elderly posyandu is alarming. The number of elderly visits to the Mawar Posyandu in the Working Area of Pendalian IV Koto Health Center is the lowest among other villages, namely 13.64%. Among the existing elderly Posyandu, Lanisa Mawar Posyandu is a posyandu located in the District Capital and has the most elderly, namely 244 people, but visits are low. This can be seen in the last 2 years where the average visit was only 10-15 people/month (2.67%). This type of research design used is a cross sectional study. The purpose of this study was to find out the factors associated with visiting the elderly to Posyandu Mawar in Pendalian Village, Pendalian IV Koto District, Rokan Hulu Regency in 2023. The population in this study were all elderly people in Pendalian Village, Pendalian IV Koto District, totaling 244 people, with a total of 244 people. The number of samples is 71 people. Data analysis was carried out univariately and bivariately with the chi square test. The results of this study found that there was a relationship between elderly visits to posyandu and knowledge (Pvalue = 0.000), health status (Pvalue= 0.000) and distance traveled (Pvalue = 0.000) . Researchers suggest that the results of this study can increase elderly visits to the Elderly Posyandu.